2018
DOI: 10.1007/s11356-018-2063-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nutritional composition of maize flour due to Tribolium castaneum infestation and application of carbon dioxide to manage this pest

Abstract: Maize flour was infested with fresh emerged Tribolium castaneum adults, and its nutritional composition was evaluated after 0, 45, and 90 days of the infestation. Furthermore, 99% carbon dioxide was applied to different developmental stages of T. castaneum for its management. There were six treatments and five replicates; for each replicate, maize flour (150 g) was taken in a 250-ml plastic jar container, insects were released in the flour, and jars were placed into the incubator at a temperature of 28 ± 1 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…This aligns with Kayode et al (2014), who stated that because ash content in millet flour is higher than in corn, wheat, and sorghum flour, millet flour is more susceptible to infestation by T. castaneum. Mehmood et al (2018) noted that they found higher ash content products that experience many pest infestation in storage. Bran flour, which contained the highest ash levels, experienced the worst pest infestation, whereas ash content is lowest in corn flour, which has little to no infestation.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with Kayode et al (2014), who stated that because ash content in millet flour is higher than in corn, wheat, and sorghum flour, millet flour is more susceptible to infestation by T. castaneum. Mehmood et al (2018) noted that they found higher ash content products that experience many pest infestation in storage. Bran flour, which contained the highest ash levels, experienced the worst pest infestation, whereas ash content is lowest in corn flour, which has little to no infestation.…”
Section: Discussionmentioning
confidence: 99%
“…For rapid kill of insects in stored products, the oxygen concentration should be less than three percent. The concentration below one percent oxygen has overturned effect for adult weevils in rice (Mehmood et al 2018). The modification of gases amounts by keeping oxygen gas at a specific concentration important for pest development may avoid the infestation of grains in the stored bin (Mehmood et al 2018;Wilkins et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration below one percent oxygen has overturned effect for adult weevils in rice (Mehmood et al 2018). The modification of gases amounts by keeping oxygen gas at a specific concentration important for pest development may avoid the infestation of grains in the stored bin (Mehmood et al 2018;Wilkins et al, 2020). The managed atmospheric technique can cause hypoxia for insects by decreasing the oxygen rate (Cheng et al 2012;2013) and hypercapnia by increasing carbon dioxide (Li et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), is a worldwide pest of stored grains (Mehmood et al, 2018;Chen Q. W. et al, 2018). It has glands that secrete a liquid which causes a moldy smell in flour and this secretion also contains the carcinogen benzoquinone (Boateng and Obengofori, 2008).…”
Section: Introductionmentioning
confidence: 99%